Effect of Intermittent Pneumatic Compression in Addition to Pharmacologic Prophylaxis for Thromboprophylaxis in Hospitalized Adult Patients: A Systematic Review and Meta-Analysis. (3rd October 2022) - Duval, Cécile; Sirois, Caroline; Savoie-White, Félix H.; Tardif, Pier-Alexandre; Bérubé, Mélanie; Turgeon, Alexis F.; Cook, Deborah J.; Lauzier, François; Moore, Lynne
Abstract : OBJECTIVES: Venous thromboembolic events (VTE) are frequent complications in hospitalized patients and a leading cause of preventable death in hospital. Pharmacologic prophylaxis is a standard of care to prevent VTE in patients at risk, the additional value of intermittent pneumatic compression (IPC) is uncertain. We aimed to evaluate the efficacy of adding IPC to pharmacologic prophylaxis to prevent VTE in hospitalized adults. DATA SOURCES: We searched the Cochrane Central Register of Controlled Trials, Embase, MEDLINE, Cumulative Index to Nursing and Allied Health Literature, ClinicalTrials.gov, and the International Clinical Trials Registry Platform from inception to July 2022. STUDY SELECTION: We included randomized controlled trials comparing the use of IPC in addition to pharmacological thromboprophylaxis to pharmacological thromboprophylaxis alone in hospitalized adults. DATA EXTRACTION: Meta-analyses were performed to calculate risk ratio (RR) of VTE, deep venous thrombosis (DVT), and pulmonary embolism (PE). We assessed the risk of bias using the Cochrane Risk of Bias Tool for Randomized Trials, Version 2 and the quality of evidence using the Grading of Recommendations Assessment, Development and Evaluation approach. DATA SYNTHESIS: We included 17 trials enrolling 8, 796 participants. The IPC was mostly applied up to the thigh and pharmacological thromboprophylaxis was primarily low-molecular-weight heparin. Adjunctive IPC was associated with a decreased risk of VTE (15 trials, RR = 0.53; 95% CI [0.35–0.81]) and DVT (14 trials, RR = 0.52; 95% CI [0.33–0.81]) but not PE (seven trials, RR = 0.73; 95% CI [0.32–1.68]). The quality of evidence was graded low, downgraded by risk of bias and inconsistency. Moderate and very low-quality evidence, respectively, suggests that adjunctive IPC is unlikely to change the risk of all-cause mortality or adverse events. Subgroup analyses indicate a more evident apparent benefit in industry-funded trials. CONCLUSIONS: Results indicate low-quality evidence underpinning the additional use of IPC to pharmacological thromboprophylaxis for prevention of VTE and DVT. Further large high-quality randomized trials are warranted to support its use and to identify patient subgroups for whom it could be beneficial.